2020
DOI: 10.1017/s0950268820000758
|View full text |Cite
|
Sign up to set email alerts
|

Development and external-validation of a nomogram for predicting the survival of hospitalised HIV/AIDS patients based on a large study cohort in western China

Abstract: The aim of this study was to develop and externally validate a simple-to-use nomogram for predicting the survival of hospitalised human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) patients (hospitalised person living with HIV/AIDS (PLWHAs)). Hospitalised PLWHAs (n = 3724) between January 2012 and December 2014 were enrolled in the training cohort. HIV-infected inpatients (n = 1987) admitted in 2015 were included as the external-validation cohort. The least absolute shrinkage and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This is probably because the China Free Antiretroviral Therapy Manual recommends aggressive regimens for special patients with complications and coinfection. This is consistent with a prior study in Guangxi, which reported that the diagnosis of tuberculosis was a beneficial factor for the survival of patients hospitalized HIV/AIDS [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is probably because the China Free Antiretroviral Therapy Manual recommends aggressive regimens for special patients with complications and coinfection. This is consistent with a prior study in Guangxi, which reported that the diagnosis of tuberculosis was a beneficial factor for the survival of patients hospitalized HIV/AIDS [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a simple-to-use nomogram for predicting the survival of hospitalised HIV/AIDS patients was published by Yuan et al . as ‘Development and external-validation of a nomogram for predicting the survival of hospitalised HIV/AIDS patients based on a large study cohort in western China’ [1]. The authors claimed the nomogram had high performance in external validation and was clinically useful.…”
mentioning
confidence: 99%
“…In the paper, it said ‘The survival of the training cohort was 94.8% and 90.8% at the 10-day and 20-day, respectively’ [1], indicating the 10-day mortality is around 5% and 20-day mortality is about 9%, which are incredibly high. Compared to the numbers in the article they cited [2], the overall in-hospital mortality rate was only 29.36 per 100 person-years [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We disagree with the authors' claim that the mortality rates in our study were incredibly high. The mortality rates at the 10-day and 20-day periods were 5.2% and 9.2%, respectively [1]; this can be compared with the overall mortality rate of hospitalised HIV/AIDS patients in the training cohort of 9.02% [1]. These rates were percentages, not person-years or person-days.…”
mentioning
confidence: 99%